Analisis Penerapan Good Corporate Governance Terhadap Kualitas Laporan Keuangan Pemerintah Desa tanete Harapan Kecamatan Cina Kabupaten Bone - Nurtasya; Muhammad Fakhri Amir; Hartas Hasbi (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
This thesis is entitled Analysis of the Implementation of Good Corporate Governance on the Quality of Financial Reports in Tanete Harapan Village, Cina District, Bone Regency. This study aims to analyze the extent to which the Implementation of Good Corporate Governance (GCG) Principles influences the Quality of Financial Reports in the Tanete Harapan Village Government, Cina District, Bone Regency. This study uses a qualitative approach with a case study method. Data were collected through in-depth interviews with village officials, direct observation of the financial report preparation process, and a review of applicable documents and regulations. The results of the study indicate that the implementation of GCG in Tanete Harapan Village has been implemented. In general, the principle of transparency has begun to be applied through the delivery of financial information to the public, although it is not yet fully accessible and understandable by villagers. The quality of the resulting financial reports is directly influenced by the successful implementation of the GCG Principles. Village financial reports show improvements in terms of timeliness and compliance with standard reporting formats. This study concludes that increasing the implementation of comprehensive GCG Principles will have a significant impact on improving the quality of village government financial reports. Therefore, concrete steps are needed in the form of increasing the capacity of village officials through training and technical assistance, strengthening the internal monitoring system, and increasing community participation in the village financial management process.